Immunogenic Properties of Streptococcus agalactiae FbsA Fragments - Papasergi, Salvatore; Lanza Cariccio, Veronica; Pietrocola, Giampiero; Domina, Maria; D’Aliberti, Deborah; Trunfio, Maria Grazia; Signorino, Giacomo; Peppoloni, Samuele; Biondo, Carmelo; Mancuso, Giuseppe; Midiri, Angelina; Rindi, Simonetta; et al. (PLOS ONE, 2013)
Several species of Gram-positive bacteria can avidly bind soluble and surface-associated fibrinogen (Fng), a property that is considered important in the pathogenesis of human infections. To gain insights into the mechanism by which group B Streptococcus (GBS), a frequent neonatal pathogen, interacts with Fng, we have screened two phage displayed genomic GBS libraries. All of the Fng-binding phage clones contained inserts encoding fragments of FbsA, a protein displaying multiple repeats. Since the functional role of this protein is only partially understood, representative fragments were recombinantly expressed and analyzed for Fng binding affinity and ability to induce immune protection against GBS infection. Maternal immunization with 6pGST, a fragment containing five repeats, significantly protected mouse pups against lethal GBS challenge and these protective effects could be recapitulated by administration of anti-6pGST serum from adult animals. Notably, a monoclonal antibody that was capable of neutralizing Fng binding by 6pGST, but not a non-neutralizing antibody, could significantly protect pups against lethal GBS challenge. These data suggest that FbsA-Fng interaction promotes GBS pathogenesis and that blocking such interaction is a viable strategy to prevent or treat GBS infections.